PENGARUH FRAKSI VOLUME FIBER GLASS TERHADAP SIFAT MEKANIK KOMPOSIT FIBER GLASS/EPOXY DENGAN METODE VARI - Mohammad Alfian Ilmy; Ahmad Adib Rosyadi; Salahuddin Junus (STATOR: Jurnal Ilmiah Mahasiswa Teknik Mesin, 2018)
The purpose of this study was to determine the optimal volume fraction in obtaining the highest tensile strength and impact resistance. In this study, the composite material consisted of an Epoxy AB777 resin as a matrix and 300 mat fiberglass as a reinforcement, with variations in vacuum pressure (0.2 and 0.5 bar) as well as fiberglass volume fraction (Vf = 30%, 35%, 40%, 45 %, 50%) to tensile strength and impact resistance. Application of Vacuum Assisted Resin Infusion (VARI) method is by drain the resin into the reinforcement which is placed in airtight mold by using vacuum pump. From the test result, the highest tensile strength is owned by composite with Vf 50% and 0.5 bar pressure is 138,18 MPa and the lowest is owned by Vf 30% with pressure 0,2 bar is 96,60 MPa. While the highest impact resistance is owned by a composite with Vf 45% with a 0.5 bar pressure is 0.191 J / mm2 and the lowest one is owned by Vf 30% with a 0.2 bar pressure is 0.098 J / mm2. It can be concluded that, (1) Greater the vacuum pressure used, greater the mechanical strength of the composite. (2) Greater the fiber volume fraction, will increase the tensile strength of fiberglass / epoxy composites. However, 45% fiber volume fraction is the optimum volume fraction for composite impact resistance. Keywords: Fiberglass / Epoxy Composite, Mechanical properties, VARI.